Development of a Volleyball Service Learning Model Through Game-Based Activities in Physical Education at Junior High School 5 Bengkulu - Aci Apriani; Hikmah Lestari (Universitas Negeri Semarang, 2026)
This research and development were based on a policy (R &D) aimed to produce a valid, practical, and effective Volleyball game base service learning model for Physical Education (PE) in Junior High School 5 Kota Bengkulu. The study used the ADDIE model (Analysis, Design, Development, Implementation and Evaluation as a design for Research and Development (R&D). Data collection techniques consisted of observation, interviews, and questionnaire surveys to obtain expert validation data and to assess the practicality of the developed product. Five prototype game-oriented volleyball service learning models were first developed depending on the students' characteristics, whereas the validation, refinement and operational results indicated that four of the models could be workplace-ready model, namely Target Zone Service Model, Service Relay Model, Hit and Cone Model and Service and Run Model. The validity by expert (a learning expert, a volleyball subject-matter professional and a media specialist) of the system showed that feasibility scores for three experts were in high 90.3%, 91.0% and 90.6% with results all falling into highly feasible. Restrained implementation proved the feasibility and favorability of the four models among teachers, as well as students' motivation for participating in activities. On the basis of these results, the game-based volleyball service learning model is regarded as feasible, acceptable and practicable, and may be an optional instructional strategy to improve volleyball service teaching in junior secondary Physical Education classes.